A Reader for Developing Writers - Buscemi, S. (United States of America MCGraw-Hill, 1996)
A reader for Developing Writers integrates principles essenial to the teaching of reqading and writing. Students learn tio rea carefully, react critically, and use their reactions as springboards for writing.
Keywords: Literature